Peculiarities of geodesic works with the use of UAVs for the needs of land management - Butenko, E.; Nevoit, N. (Land Management, Cadastre and Land Monitoring, 2021)
It is determined and substantiated that the most popular type of survey activity for land management is the use of unmanned aerial vehicles, as most traditional methods of geodetic surveys are not effective enough today, they can not provide the required measurement accuracy, especially for landowners and land users. , is very important. An approximate algorithm for the use of unmanned aerial vehicles to solve geodetic problems of land management of united territorial communities, which includes stages of preparation from re-survey to create a digital terrain model, the advantages of using unmanned aerial vehicles over traditional types of geodetic surveys. analyzed a number of features of the use of unmanned aerial vehicles in geodetic surveying for the needs of OTG land management, calculated the economic efficiency of this type of geodetic surveys on a specific example, namely the village of Gamaliyivka Pustomyty district of Lviv region and compared the comparison of traditional costs and time training and the use of unmanned aerial vehicles. At the same time, the ways of improving the process of aerial photography with the help of UAVs are presented both at the normative and at the organizational and technical level. namely, the settlement of Gamaliyivka, Pustomyty district, Lviv region, and a comparison of the cost of time and money in comparison with the traditional method of geodetic surveys and the use of unmanned aerial vehicles. At the same time, the ways of improving the process of aerial photography with the help of UAVs are presented both at the normative and at the organizational and technical level. namely, the settlement of Gamaliyivka, Pustomyty district, Lviv region, and a comparison of the cost of time and money in comparison with the traditional method of geodetic surveys and the use of unmanned aerial vehicles. At the same time, the ways of improving the process of aerial photography with the help of UAVs are presented both at the normative and at the organizational and technical level.Keywords: unmanned aerial vehicles, geodetic surveys, aerial photography, land management works, planned-vistona basis, economic efficiency, orthophotoplan